Breeding and winter site fidelity among eleven Neotropical Austral migrant bird species - Jahn, A.E. (2009)
Very little information currently exists on site fidelity patterns among Neotropical Austral migratory birds, which migrate wholly within South America. We banded migratory birds at three sites in South America, one located in the tropics and two at south temperate latitudes. We document breeding site fidelity among seven species and winter site fidelity among four species. Knowledge of patterns of site fidelity among migratory birds in South America is important for understanding the constraints affecting their populations throughout the annual cycle and ultimately for conservation planning. Accepted 8 April 2009. © The Neotropical Ornithological Society.